1983
DOI: 10.2527/jas1983.571130x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Minerals in Tissues of Pigs from Dams Fed Different Levels of Dietary Zinc

Abstract: Effects on the tissue mineral concentrations of pigs from sows fed four dietary Zn levels were studied. A male and a female from first- and second-parity litters were killed at 1 and 21 d of age. The dams were fed a corn-soybean meal basal diet supplemented with 0, 50, 500 or 5,000 ppm Zn from 30 kg body weight until completion of the second lactation. Pigs from sows fed 5,000 ppm additional zinc had heavier liver, heart, thyroid and adrenal weights relative to their body weight than did pigs from sows on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
1
2

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 0 publications
6
30
1
2
Order By: Relevance
“…Colostrum and milk Zn concentration seem to be maintained over a wide range of dietary Zn intakes (Earle and Stevenson, 1965;Courtney Moore et al, 1984;Krebs, 1998;Kelleher and Lönnerdal, 2005), and only when Zn was fed at 3-4 times the recommended dose for sows, in colostrum and milk Zn concentrations increased (Kirchgessner et al, 1980). Other authors reported increased concentrations of Zn in sow milk and piglet liver, kidney and pancreas, accompanied by a decrease in Cu concentration in sow milk and piglet liver, pancreas and muscle when excessive dietary Zn (5000 ppm) was supplied (Hill et al, 1983a(Hill et al, , 1983b.…”
Section: Discussionmentioning
confidence: 91%
“…Colostrum and milk Zn concentration seem to be maintained over a wide range of dietary Zn intakes (Earle and Stevenson, 1965;Courtney Moore et al, 1984;Krebs, 1998;Kelleher and Lönnerdal, 2005), and only when Zn was fed at 3-4 times the recommended dose for sows, in colostrum and milk Zn concentrations increased (Kirchgessner et al, 1980). Other authors reported increased concentrations of Zn in sow milk and piglet liver, kidney and pancreas, accompanied by a decrease in Cu concentration in sow milk and piglet liver, pancreas and muscle when excessive dietary Zn (5000 ppm) was supplied (Hill et al, 1983a(Hill et al, , 1983b.…”
Section: Discussionmentioning
confidence: 91%
“…The Zn concentration in liver tissue was conducted using a method described by Shelton and Southern [45] and Hill et al [46] (Table 5). Zn was separately determined in each liver sample taken from each of the birds.…”
Section: Determination Of Zn Concentration In Chicken Liver Tissuementioning
confidence: 99%
“…Uniform samples were cut from tissues, wet-digested using nitric-perchloric acid, and then diluted with deionized-distilled water for analyses of minerals [25]. Contents of Zn, iron (Fe), copper (Cu), and manganese (Mn) were analyzed with flame atomic absorption spectrophotometry (AA-6300, Shimadzu, Tokyo, Japan).…”
Section: Determination Of Mineral Concentrationmentioning
confidence: 99%